Maternal iron status in early pregnancy and birth outcomes: insights from the Baby's Vascular health and Iron in Pregnancy study - Alwan, Nisreen A. (Br J Nutr, 2015)
Fe deficiency anaemia during early pregnancy has been linked with low birth weight and preterm birth. However, this evidence comes mostly from studies measuring Hb levels rather than specific measures of Fe deficiency. The present study aimed to examine the association between maternal Fe status during the first trimester of pregnancy, as assessed by serum ferritin, transferrin receptor and their ratio, with size at birth and preterm birth. In the Baby VIP (Baby's Vascular health and Iron in Pregnancy) study, we recruited 362 infants and their mothers after delivery in Leeds, UK. Biomarkers were measured in maternal serum samples previously obtained in the first trimester of pregnancy. The cohort included sixty-four (18 %) small for gestational age (SGA) babies. Thirty-three babies were born preterm (9 %; between 34 and 37 weeks). First trimester maternal Fe depletion was associated with a higher risk of SGA (adjusted OR 2·2, 95 % CI 1·1, 4·1). This relationship was attenuated when including early pregnancy Hb in the model, suggesting it as a mediator (adjusted OR 1·6, 95 % CI 0·8, 3·2). For every 10 g/l increase in maternal Hb level in the first half of pregnancy the risk of SGA was reduced by 30 % (adjusted 95 % CI 0, 40 %); levels below 110 g/l were associated with a 3-fold increase in the risk of SGA (95 % CI 1·0, 9·0). There was no evidence of association between maternal Fe depletion and preterm birth (adjusted OR 1·5, 95 % 0·6, 3·8). The present study shows that depleted Fe stores in early pregnancy are associated with higher risk of SGA.